Kinesin-1-mediated axonal transport of CB1 receptors is required for cannabinoid-dependent axonal growth and guidance - Saez, Trinidad María de Los Milagros (2020)
Endocannabinoids (eCB) modulate growth cone dynamics and axonal pathfinding through the stimulation of cannabinoid type-1 receptors (CB1R), the function of which depends on their delivery and precise presentation at the growth cone surface. However, the mechanism involved in the axonal transport of CB1R and its transport role in eCB signaling remains elusive. As mutations in the kinesin-1 molecular motor have been identified in patients with abnormal cortical development and impaired white matter integrity, we studied the defects in axonal pathfinding and fasciculation in mice lacking the kinesin light chain 1 (Klc1^-/-^) subunit of kinesin-1. Reduced levels of CB1R were found in corticofugal projections and axonal growth cones in Klc1^-/-^ mice. By live-cell imaging of CB1R-eGFP we characterized the axonal transport of CB1R vesicles and described the defects in transport that arise after KLC1 deletion. Cofilin activation, which is necessary for actin dynamics during growth cone remodeling, is impaired in the Klc1^-/-^ cerebral cortex. In addition, Klc1^-/-^ neurons showed expanded growth cones that were unresponsive to CB1R-induced axonal elongation. Together, our data reveal the relevance of kinesin-1 in CB1R axonal transport and in eCB signaling during brain wiring.